Mathématiques
ChloeKr
10

Aider moi svp l'exercice n.53, je n'y arrive pas !!

+1
(2) Réponses
michalakk

(3x-5)² - (3x-5)(x+4)= 9x²-30x+25-3x²+12-5x-20=6x² -23x +5 (3x-5)(3x-5+x+4) = (3x-5)(4x-1) pour x =1 (3x1-5)x(4x1-1) = -1x3=-3 pour x=4.5 (3x4.5-5)(4x4.5-1)= 8.5 x17=144.5

lucabp22

 a)  F   = (3x-5)^2 - (3x-5)(x+4)       = (3x-5)(3x-5) - (3x-5)(x+4)       = 9x^2 -15x -15x+25 - (3x^2+12x -5x -20)       =  9x^2 -30x + 25 - ( 3x^2+ 7x - 20)       = 9x^2 - 30x + 25 -3x^2 -7x +20       = 6x^2 -37x +45      

Ajouter une réponse